Determinan Kepatuhan Pegawai Kantor Pemerintahan Balai Kota Malang Dalam Membayar Pajak - Safitri, Safitri; Afifudin, Afifudin; Nandiroh, Umi (Universitas Islam Malang, 2023)
This study aims to determine the partial and simultaneous influence between to determine and analyze the effect of tax services, tax knowledge, and tax sanctions on taxpayer compliance in paying taxes. This research is a type of explanatory research using a quantitative approach. The population in this study is employees of the Malang City Hall Government Office in the General Secretariat. And sampling in this study through non-probability sampling techniques of quota sampling type. Quota sampling is a sampling technique from a population that has certain characteristics to the desired number (quota). It is known that the number of respondents was 38 respondents, with sampling using purposing sampling. In data collection using questionnaire instruments. Based on the results of the study, it is known that taxation, tax knowledge, and tax sanctions simultaneously have a significant positive effect on individual taxpayer compliance in paying taxes. Tax services have a significant positive effect on individual taxpayer compliance in paying taxes. Taxation knowledge has no effect on individual taxpayer compliance in paying taxes. Based on the R2 calculation, it was found that 57.5% of tax service variables, tax knowledge, tax sanctions affected the compliance of individual taxpayers in paying taxes, while the other 42.5% were influenced by other independent variables that were not included in this study.Keywords: Tax services, knowledge of taxation, tax sanctions, taxpayer compliance and paying taxes